Redundancy and interaction of thrombin- and collagen-mediated platelet activation in tail bleeding and carotid thrombosis in mice - Bynagari-Settipalli, Yamini S. (Arterioscler Thromb Vasc Biol, 2014)
OBJECTIVE: Current antiplatelet strategies to prevent myocardial infarction and stroke are limited by bleeding risk. A better understanding of the roles of distinct platelet-activating pathways is needed. We determined whether platelet activation by two key primary activators, thrombin and collagen, plays distinct, redundant, or interacting roles in tail bleeding and carotid thrombosis in mice. APPROACH AND RESULTS: Platelets from mice deficient for the thrombin receptor Par4 and the collagen receptor GPVI lack responses to thrombin and collagen, respectively. We examined tail bleeding and FeCl(3)-induced carotid artery occlusion in mice lacking Par4, GPVI or both. We also examined a series of Par mutants with increasing impairment of thrombin signaling in platelets. Ablation of thrombin signaling alone by Par4 deficiency increased blood loss in the tail bleeding assay and impaired occlusive thrombus formation in the carotid occlusion assay. GPVI deficiency alone had no effect. Superimposing GPVI deficiency upon Par4 deficiency markedly increased effect size in both assays. In contrast to complete ablation of thrombin signaling, 9- and 19-fold increases in EC(50) for thrombin-induced platelet activation had only modest effects. CONCLUSION: The observation that loss of Par4 uncovered large effects of GPVI deficiency implies that Par4 and GPVI made independent, partially redundant contributions to occlusive thrombus formation in the carotid and to hemostatic clot formation in the tail under the experimental conditions examined. At face value, these results suggest that thrombin- and collagen-induced platelet activation can play partially redundant roles despite important differences in the how these agonists are made available to platelets.